LEACH protocol based security mechanism for Sybil attack detection - CHEN Shan-shan1; YANG Geng2; CHEN Sheng-shou2 (Tongxin xuebao)
Low energy adaptive clustering hierarchy（LEACH） could effectively reduce energy consumption of wireless sensor network（WSN）.However,a novel security mechanism was proposed based on LEACH protocol called LEACH-S in order to improve the security performance of WSN.The mechanism adopted a received signal strength indicator（RSSI） based policy for Sybil attack detection in WSN,and a reasonable threshold was chosen to initialize Sybil attack detection strategy in which case attack may occur with high possibility.The simulation results show that the mechanism can detect Sybil attack effectively at the cost of low energy consumption.